Severe outcomes of pediatric perioperative adverse events occurring in operating rooms compared to off‐site anesthetizing locations in the Wake Up Safe Database. Issue 1 (30th December 2018) - Uffman, Joshua C.; Tumin, Dmitry; Beltran, Ralph J.; Tobias, Joseph D.
Summary: Background: Anesthesia services are frequently provided outside of the traditional operating room environment for children. It is unclear if adverse events which occur in off‐site anesthetizing locations result in more severe outcomes compared to events in traditional operating rooms. Aim: We used a multi‐institutional registry of pediatric patients to compare outcomes of perioperative adverse events between location types. Methods: De‐identified data from 24 pediatric tertiary care hospitals participating in the Wake Up Safe registry during 2010‐2015 were analyzed. Peri‐procedural adverse events occurring in operating rooms or off‐site locations were included. The primary outcome was whether the adverse event was severe, defined as requiring escalation of care or resulting in temporary or significant harm. Multivariable logistic regression was used to compare location type (operating room vs. off‐site) and the likelihood of a severe outcome among reported events. Results: There were 1594 adverse events, of which 362 were associated with off‐site anesthetizing locations. In multivariable logistic regression, off‐site location was associated with greater odds of severe adverse event outcome (adjusted odds ratio, 1.31; 95% confidence interval: 1.01, 1.69; P  = 0.044). Comparing adverse events in cardiac catheterization suites to events in operating rooms confirmed higher odds of severe outcome in the former group (adjusted odds ratio = 1.48; 95% confidence interval: 1.05, 2.08; P  = 0.025), while this difference was not found for other off‐site locations. Conclusion: Multivariable analysis of a large registry revealed a greater likelihood of severe outcome for adverse events occurring in cardiac catheterization suites (but not other out of the OR sites), compared to adverse events occurring in the operating room. Additional prospective studies are needed which better control for patient and environmental characteristics and their effect on severe outcomes after anesthesia.